Member Participation in the Management of Women Farmer Group Activities - Wulandari Retno; Kusumaningrum Alma (E3S Web of Conferences, 2024)
The Women Farmer’s Group was formed to improve the ability of farmers and their families in agriculture. Women's participation is expected to improve the community's economy through horticultural businesses. The growth of the Merapi Asri Women's Farmer Group can be seen from the increase in the number of members. This study uses a quantitative descriptive method and was conducted in January 2024 involving 50 administrators and members as respondents who were taken by census. Analysis with the Spearman Rating Correlation Coefficient shows high participation in planning, implementation, utilization of results, and evaluation of activities. This group of women farmers develops horticultural farming businesses ranging from vegetables to fruits. Although there were variations in family support, leisure time, extension roles, and economic motivation, all factors showed a close relationship with the effectiveness of activities. The role of extension workers has a strong correlation, especially at the implementation stage. It is recommended to improve communication and collaboration between members to encourage participation.